2000
DOI: 10.1021/jf990669t
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Formation of Oxidative Volatile Components in Fermented Cucumbers by Ascorbic Acid and Turmeric

Abstract: Two naturally occurring antioxidants, ascorbic acid and turmeric, were effective in inhibiting formation of hexanal, (E)-2-penenal, (E)-2-hexenal, (E)-2-heptenal, and (E)-2-octenal when slurries of fermented cucumber tissue were exposed to oxygen. Added ascorbic acid prevented formation of most of these oxidative aldehydes at 175 ppm or greater. Turmeric, which is used commercially as a yellow coloring in cucumber pickle products, was found to almost completely prevent aldehyde formation at 40 ppm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In the present study, the lack of significant differences in the concentrations of EPA and DHA between the two curcumin treatments suggested curcumin was very effective even at the low concentration. Zhou et al (39) reported that 40 ppm curcumin could completely inhibit aldehyde formation in fermented cucumber tissue that was exposed to oxygen. Jayaprakasha et al (13) observed that lipid peroxidation of linoleic acid emulsion was inhibited with 0.01% curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the lack of significant differences in the concentrations of EPA and DHA between the two curcumin treatments suggested curcumin was very effective even at the low concentration. Zhou et al (39) reported that 40 ppm curcumin could completely inhibit aldehyde formation in fermented cucumber tissue that was exposed to oxygen. Jayaprakasha et al (13) observed that lipid peroxidation of linoleic acid emulsion was inhibited with 0.01% curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…A lower pH value for preserves (Table 3) reduces the activity of ascorbinase [11,14,15], therefore no such rapid reduction of the vitamin C content has been observed. The presence of vitamin C in pickle and brine solutions (Table 4) can be accounted for by water solubility of this vitamin.…”
Section: Methodsmentioning
confidence: 99%
“…For a long time, curcumin has been applied as an anti-inflammatory, 1) anti-oxidative, [2][3][4] and anti-carcinogenic 5) compound. The multiple therapeutic effects of curcumin result from its ability to modulate enzyme activities and gene expression.…”
mentioning
confidence: 99%